Efek Ekstrak Etanol Kulit Batang Sirsak Terhadap Penurunan Kadar Gula Darah dan Kolesterol - Dian Ayu Juwita; Husni Muchtar; Dolly Martha (Jurnal Sains Farmasi & Klinis, 2015)
This study aims to determine effect of the ethanolic extract of soursop stembarks in the increasing of blood glucose and cholesterol levels. Maceration technique has been used to extract the soursop stembarks with ethanol 96% as a solvent extraction. Furthermore, the ethanolic extract of soursop stembarks was prepared in a suspension form with Na CMC 0.5 % as a suspending agent. The suspension was administered orally at dose of 50, 100, 300, 1000 mg/kg BW daily to white male mice for seven days. The level of blood sugar and cholesterol were measured at 8th day using digital tools Nesco®Multicheck. The result showed that the blood glucose level in mice at dose of 50, 100, 300, 1000 mg/KgBW were 123.25, 129.75, 132.25, 121.25 mg/dl. The cholesterol level mice at dose of 50, 100. 300, 1000 mg/kg BW were 156.5, 118.5, 149.75, 156.75 mg/dl respectively. Biostatistically, the ethanolic extract of soursop stembark showed the decreasing of cholesterol level significantly (p <0.05), but not significant to reduce the blood glucose level (p >0.05).